Determination of fighting styles of qualified veteran boxers based on cluster analysis of biomechanical and psychophysiological indicators - V.Yu. Kozin; O.Ye. Falova; M. Cretu; M. Cieślicka (H.S. Skovoroda Kharkiv National Pedagogical University, 2021)
Purpose: to reveal the styles of fighting veteran boxers on the basis of a multivariate analysis of psychophysiological and biomechanical indicators. Material and methods. The study involved 42 qualified veteran boxers (age 45-50 years). As research methods, we used a biomechanical analysis of the indicators of the speed of movement of various points and the values ​​of the angles in the joints when performing a direct blow by boxers. The psychophysiological method was used to determine the time of a simple and complex reaction under standard conditions and in various testing modes. We used the method of cluster analysis to distribute athletes into groups using the SPSS - 17.0 program. Within the groups, the athletes are as similar as possible to each other in terms of the analyzed indicators, and between the groups they differ as much as possible. The analysis of the groups of athletes obtained with the help of cluster analysis made it possible to identify athletes with the following styles of fighting: tempo, game, power. Results. Cluster analysis of psychophysiological and biomehanical testing showed the presence of 3 groups of athletes. The clusters were named as follows: Cluster 1 - "Speed and coordination endurance", corresponds to the boxers of the pace of the fight; Cluster 2 - "Speed", corresponds to the boxers of the game style of fighting; Cluster 3 - "Strength and speed", corresponds to the boxers of the pace of the fight. Biomechanical features of boxers of different styles of fighting are reflected in the trajectories of the points of the fist, elbow, knee. Conclusions. The results of this study should be used when planning the individual training of athletes in boxing and to determine the optimal style of competitive competition for qualified veteran boxers. The proposed methods of psychophysiological and biomechanical testing to determine the individual characteristics of boxers are an effective, fairly accessible and convenient tool for revealing the predisposition of boxers to a certain style of fighting.